A Hierarchically Encoded Data Storage Device with Controlled Transiency. Issue 20 (8th April 2022) - Wei, Shuai; Jiang, Jianjuan; Sun, Long; Li, Jianxing; Tao, Tiger H.; Zhou, Zhitao
Abstract: In the era of information explosion, high‐security and high‐capacity data storage technology attracts more and more attention. Physically transient electronics, a form of electronics that can physically disappear with precisely controlled degradation behaviors, paves the way for secure data storage. Herein, the authors report a silk‐based hierarchically encoded data storage device (HEDSD) with controlled transiency. The HEDSD can store electronic, photonic, and optical information simultaneously by synergistically integrating a resistive switching memory (ReRAM), a terahertz metamaterial device, and a diffractive optical element, respectively. These three data storage units have shared materials and structures but diverse encoding mechanisms, which increases the degree of complexity and capacity of stored information. Silk plays an important role as a building material in the HEDSD thanks to its excellent mechanical, optical, and electrical properties and controlled transiency as a naturally extracted protein. By controlling the degradation rate of storage units of the silk‐based HEDSD, different degradation modes of the HEDSD, and multilevel information encryption/decryption have been realized. Compared with the conventional memory devices, as‐reported silk‐based HEDSD can store multilevel complex information and realize multilevel information encryption and decryption, which is highly desirable to fulfill the future demands of secure memory systems and implantable storage devices. Abstract : A hierarchically encoded data storage device consisting of resistive switching memory, electromagnetic (EM) metamaterial, and diffractive optical element is reported in this paper. The storage devices can be used to store hybrid information including electronic information, EM information, and optical information. It also exhibits controllable degradation manners in vitro and in vivo, which expands the applications in bio‐implantable electronics.